2005
DOI: 10.1002/dvdy.20499
|View full text |Cite
|
Sign up to set email alerts
|

Differential levels of tissue hypoxia in the developing chicken heart

Abstract: Tissue hypoxia plays a critical role in normal development, including cardiogenesis. Previously, we showed that oxygen concentration, as assessed by the hypoxia indicator EF5, is lowest in the outflow tract (OFT) myocardium of the developing chicken heart and may be regulating events in OFT morphogenesis. In this study, we identified additional areas of the embryonic chicken heart that were intensely positive for EF5 within the myocardium in discrete regions of the atrial wall and the interventricular septum (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 63 publications
3
60
0
Order By: Relevance
“…9) at ED5 (30% apex-to-base in hypoxic, N 5 10) or ED6 (20%, N 5 5) but apex-to-base activation was present in all 8 hypoxic hearts examined at ED7 (stage 31; P 5 0.008, Chi-square test). Likewise, no differences were spotted in the location of atrial pacemaker (Sedmera et al, 2006), which was shown previously to colocalize with region of increased tissue hypoxia in the vicinity of sinoatrial nodal artery (Wikenheiser et al, 2006). Immunohistochemical examination of the hearts did not reveal any remarkable differences between normoxic and hypoxic hearts; HNK1, marker for neural crest that stains the proximal part of the ventricular conduction system showed normal expression, whereas the PSA-NCAM antibody did not react with quail tissue using protocol with paraffin sections, but stained identically processed chick tissue that served as a positive control (data not shown).…”
Section: Effect Of Hypoxia On Conduction System Maturationmentioning
confidence: 50%
See 2 more Smart Citations
“…9) at ED5 (30% apex-to-base in hypoxic, N 5 10) or ED6 (20%, N 5 5) but apex-to-base activation was present in all 8 hypoxic hearts examined at ED7 (stage 31; P 5 0.008, Chi-square test). Likewise, no differences were spotted in the location of atrial pacemaker (Sedmera et al, 2006), which was shown previously to colocalize with region of increased tissue hypoxia in the vicinity of sinoatrial nodal artery (Wikenheiser et al, 2006). Immunohistochemical examination of the hearts did not reveal any remarkable differences between normoxic and hypoxic hearts; HNK1, marker for neural crest that stains the proximal part of the ventricular conduction system showed normal expression, whereas the PSA-NCAM antibody did not react with quail tissue using protocol with paraffin sections, but stained identically processed chick tissue that served as a positive control (data not shown).…”
Section: Effect Of Hypoxia On Conduction System Maturationmentioning
confidence: 50%
“…The interventricular septum is also site of conduction system formation, correlating with hypoxic regions (Wikenheiser et al, 2006). The functionality of conduction system can be inferred from optical mapping of epicardial activation patterns Sedmera et al, 2006).…”
Section: Effect Of Hypoxia On Conduction System Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that a gradient of hypoxia across the ventricular wall corresponds with the HIF-1-responsive VEGF gene expression both in transcript and protein levels and endothelial tube formation (Tomanek et al, 1999) and that the perturbation of hypoxia can lead to abnormal coronary vascular development (IvnitskiSteele et al, 2004). Our most recent findings for EF5 and HIF-1␣ staining in the chicken embryo heart (Wikenheiser et al, 2006) suggest that other regions in addition to the OFT myocardium are hypoxic and correlate with regions that have been shown to exhibit apoptosis in chicken and mouse embryos such as the IVS (Cheng et al, 2002;Sharma et al, 2004). Furthermore, ambient hypoxia enhances the expression of the HIF-1-regulated gene VEGF in avian systems (Tomanek et al, 2003).…”
Section: Apoptosis and Hypoxic Tissuesmentioning
confidence: 55%
“…The last step, involving differentiation and patterning of the arterial and venous parts of the coronary system, occurs after the connection to circulation and is probably in part controlled by the hemodynamic signals from the lumen. Differential hypoxia of the myocardium and subsequent activation of hypoxia-inducible factors such as HIF-1 may play a role in organizing the large vessels of the coronaries at the atrioventricular and interventricular sulci (Wikenheiser et al, 2006). Much of our knowledge about the coronary development comes from studies in the avian systems, in particular the Japanese quail (Coturnix coturnix japonica).…”
mentioning
confidence: 99%